2014
DOI: 10.1111/nph.12783
|View full text |Cite
|
Sign up to set email alerts
|

Herbivory and floral signaling: phenotypic plasticity and tradeoffs between reproduction and indirect defense

Abstract: SummaryPlant defense against herbivores may compromise attraction of mutualists, yet information remains limited about the mechanisms underlying such signaling tradeoffs.Here, we investigated the effects of foliar herbivory by two herbivore species on defense compounds, floral signaling, pollinator and parasitoid attraction, and seed production.Herbivory generally reduced the quantity of many floral volatile organic compounds VOCs) in Brassica rapa. By contrast, floral color, flower diameter, and plant height … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
200
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(209 citation statements)
references
References 47 publications
4
200
1
4
Order By: Relevance
“…Before olfactometer tests, rubber septa (GR-2, 5 mm Supelco, Bellefonte, PA, USA) were soaked in the synthetic floral blend solution for 1 h, then were allowed to dry for 4 h. The concentration of each compound in the solution was adjusted so that the emission rate of each compound from a septa was comparable to one inflorescence (ca. 30 flowers) of B. rapa [41] Septa were then placed above the chosen treatment plant just prior to the tests, using a fine wire mesh to fix them at the desired location inside the olfactometer. Fine wire mesh was also added to the treatments without synthetic floral blends in order to account for the potential effects of wire odors.…”
Section: Methodsmentioning
confidence: 99%
“…Before olfactometer tests, rubber septa (GR-2, 5 mm Supelco, Bellefonte, PA, USA) were soaked in the synthetic floral blend solution for 1 h, then were allowed to dry for 4 h. The concentration of each compound in the solution was adjusted so that the emission rate of each compound from a septa was comparable to one inflorescence (ca. 30 flowers) of B. rapa [41] Septa were then placed above the chosen treatment plant just prior to the tests, using a fine wire mesh to fix them at the desired location inside the olfactometer. Fine wire mesh was also added to the treatments without synthetic floral blends in order to account for the potential effects of wire odors.…”
Section: Methodsmentioning
confidence: 99%
“…Such effects can be mediated by decreased flower-or inflorescence size (Barber et al 2012;Lehtila and Strauss 1997;Poveda et al 2005), amounts of rewards, secondary defense metabolites present in nectar (Adler et al 2006), induced repellent volatile organic compounds (VOCs; Kessler and Halitschke 2009;Zangerl and Berenbaum 2009), or reduced attractive floral VOCs (Bruinsma et al 2014;Pareja et al 2012;Schiestl et al 2014). In our study, however, no ecological trade-offs were detectable; we found no short-time effects of leaf herbivory on floral display (i.e., flower number, corolla diameter, petal length, and calyx length), or reward in Silene flowers (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Comparable effects have been found in flower-visitor interactions; herbivory-induced changes e.g. in floral scent, morphology and nectar, have been shown to alter flower visitor behavior (Schiestl et al 2014;Bruinsma et al 2014;Hoffmeister et al 2015). Depending on the animal and plant species this resulted in either increased or decreased visitation frequencies (Lucas-Barbosa et al 2013;Hoffmeister et al 2015).…”
Section: Introductionmentioning
confidence: 98%